Get ready for IELTS : Writing, Pre-intermediate A2+ - Aish, Fiona; Tomlinson, Jo. (Tp.HCM : Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2013)
Hobbies and interests; Education; Culture; ...
Keywords: English language; IELTS; English language -- Written English -- Examinations -- Study guides; English language -- Textbooks for foreign speakers